A mother's love : a novel [compact disc, unabridged] - Steel, Danielle (Recorded Books, 2025)
A devoted mother, Halley Holbrook, faces an empty nest and reflects on her life. After her daughters move to Los Angeles, she books a trip to Paris. There, she meets Bart Warner and begins to feel more like herself. When a thief steals her handbag and harasses her, old ghosts reawaken. With Bart's help, she chooses a bold course of action. Danielle Steel's novel is a story of emotional resilience and letting go.